Menstrual Disorders of 3-Month Contraceptive Injection Acceptors in Independent Midwife Practice in Binangun District, Blitar Regency - Monica, Laily Prima; Ulfa, Maria; Fata, Ulfa Husnul (STIKes Patria Husada Blitar, 2024)
The contraceptive injection method using medroxyprogesterone (a type of progestin) which is injected every 3 months has side effects, namely menstrual cycle disorders. The longer the injection is used, the more women do not menstruate and also experience irregular bleeding. This was a descriptive study that aimed to see the menstrual disorders of 3-month contraceptive injection acceptors at the Binangun Midwife Independent Practice, Blitar Regency. The population in this study were active contraceptive injection acceptors who visited the Binangun Midwife Independent Practice, Blitar Regency, with an average population of 87 people. The sample in this study was 3-month contraceptive injection acceptors who met the inclusion and exclusion criteria. The number of samples in this study was 66 people with a purposive sampling technique. The data analysis used frequency distribution to describe menstrual disorders experienced by 3-months Contraceptive Injection acceptors. The results of this study indicated that the menstrual disorders experienced by 3-months contraceptive injection acceptors were mostly amenorrhea, namely 53 people (80.3%). While bleeding outside of menstruation was 10 people (15.2%) and the rest, namely 3 people (4.5%) did not experience menstrual disorders. The 3-months contraceptive injection method has been proven effective in preventing pregnancy, the therapy needs to pay attention to the side effects caused so as not to interfere with the 3-months Contraceptive Injection acceptors.